Predictive genomics DNA profiling for athletic performance. - Kambouris, M.; Ntalouka, F.; Ziogas, G.; Maffulli, N. (Recent Patents on DNA & Gene Sequences, 2012)
Genes control biological processes such as muscle, cartilage and bone formation, muscle energy production and metabolism (mitochondriogenesis, lactic acid removal), blood and tissue oxygenation (erythropoiesis, angiogenesis, vasodilatation), all essential in sport and athletic performance. DNA sequence variations in such genes confer genetic advantages that can be exploited, or genetic 'barriers' that could be overcome to achieve optimal athletic performance. Predictive Genomic DNA Profiling for athletic performance reveals genetic variations that may be associated with better suitability for endurance, strength and speed sports, vulnerability to sports-related injuries and individualized nutritional requirements. Knowledge of genetic 'suitability' in respect to endurance capacity or strength and speed would lead to appropriate sport and athletic activity selection. Knowledge of genetic advantages and barriers would 'direct' an individualized training program, nutritional plan and nutritional supplementation to achieving optimal performance, overcoming 'barriers' that results from intense exercise and pressure under competition with minimum waste of time and energy and avoidance of health risks (hypertension, cardiovascular disease, inflammation, and musculoskeletal injuries) related to exercise, training and competition. Predictive Genomics DNA profiling for Athletics and Sports performance is developing into a tool for athletic activity and sport selection and for the formulation of individualized and personalized training and nutritional programs to optimize health and performance for the athlete. Human DNA sequences are patentable in some countries, while in others DNA testing methodologies [unless proprietary], are non patentable. On the other hand, gene and variant selection, genotype interpretation and the risk and suitability assigning algorithms based on the specific Genomic variants used are amenable to patent protection.